Evolution and prognosis of intramural aortic hematoma. Insights from a midterm cohort study. (15th December 2017) - Ferrera, Carlos; Vilacosta, Isidre; Gómez-Polo, Juan Carlos; Villanueva-Medina, Sara; Cabeza, Beatriz; Ortega, Luis; Cañadas, Victoria; Carnero-Alcázar, Manuel; Martínez-López, Isaac; Maroto-Castellanos, Luis; Serrano-Hernando, Francisco Javier
Abstract: Background: Although several hypotheses have been proposed, the true origin and pathogenesis of aortic intramural hematoma (IMH) remain unclear. Evolution of patients with aortic IMH is highly variable. Progression to classic aortic dissection, aneurysm or to complete resolution have been described. Our purpose was to assess in-hospital and mid-term evolution of patients with aortic IMH. Methods: From 2000 to 2015, 40 patients with aortic IMH were prospectively and consecutively recruited in a tertiary care referral center. Aortic IMH was defined as the presence of a circular or crescent-shaped thickening of the aortic wall (≥ 5 mm) in the absence of detectable blood flow inside, within the context of acute aortic syndrome. Results: Twenty three patients (57.5%) had type A, and 17 (42.5%) type B IMH. Up to 34.7% of patients with type A and 47.1% with type B IMH showed intimal tears in the imaging test at admission. In-hospital mortality was higher in the type A IMH group. All-cause mortality after discharge was 20%, without significant differences among groups. Out of hospital death was related to the aortic pathology in just one patient. At follow-up, radiological persistence of IMH was observed in 35.7% of patients with type A and 60% of those with type B IMH. Conclusions: IMH related mortality takes place primarily during the acute phase of the disease. Clinical evolution after discharge is favorable, either in cases of reabsorption or persistence of the IMH. Imaging test findings rekindle the debate on the true training mechanism of the aortic IMH. Highlights: In-hospital mortality associated with aortic intramural hematoma is exceedingly high. Mortality dramatically decreases after discharge. A large proportion of patients showed intimal tears in imaging test at admission. Imaging test findings rekindle the debate on the training mechanism of this disease. Blood pressure control is essential to prevent complications of intramural hematoma.